2022
DOI: 10.31616/asj.2021.0123
|View full text |Cite
|
Sign up to set email alerts
|

Thorough Comparative Analysis of Stand-Alone Cage and Anterior Cervical Plate for Anterior Cervical Discectomy and Fusion in the Treatment of Cervical Degenerative Disease: A Systematic Review and Meta-analysis

Abstract: In this systematic review and meta-analysis, we aim to thoroughly describe and objectively compare the efficacy of anterior cervical plate (ACP) and stand-alone cage (SAC). Although recognized as an effective procedure for cervical degenerative disease (CDD), a debate between the methods of anterior cervical discectomy and fusion exists. ACP provides stability to the fusion construct; however, some complications have been reported, such as dysphagia, adjacent disc disease, and soft tissue injury. To overcome t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
(62 reference statements)
1
3
0
Order By: Relevance
“…37 According to several reviews of the literature, functional outcomes for primary APC and SAAS using JOA, NDI, and VAS are comparable. [38][39][40][41][42][43][44] Our meta-analysis confirmed the same findings as primary APC and SAAS, as both lead to improvements in JOA, VAS, and NDI in revision surgery. This similarity should be interpreted with caution due to the inherent differences between primary and revision surgery.…”
Section: Efficacy and Functional Outcomessupporting
confidence: 81%
“…37 According to several reviews of the literature, functional outcomes for primary APC and SAAS using JOA, NDI, and VAS are comparable. [38][39][40][41][42][43][44] Our meta-analysis confirmed the same findings as primary APC and SAAS, as both lead to improvements in JOA, VAS, and NDI in revision surgery. This similarity should be interpreted with caution due to the inherent differences between primary and revision surgery.…”
Section: Efficacy and Functional Outcomessupporting
confidence: 81%
“…Dysphagia frequently occurs following anterior approach-related cervical surgeries, including ACDF and ACCF [ 16 - 18 ]. In the previous study, dysphagia was the most common complication following ACDF, observed in 9.5% of patients [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…This has historically provided successful arthrodesis and restored segmental stability. Since the 1980s, anterior plating has been common practice, improving the fusion rate and maintaining cervical lordosis in both single-level and multi-level cases ​[ 3 , 6 ]. However, plating is not without complications, with multiple studies reporting significant incidences of dysphagia and screw migration ​[ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite providing superior bone fusion and cervical alignment, anterior plating is not without complications. Due to possible soft tissue irritation, dysphagia is relatively common in patients with anterior plating compared to those treated solely with the Cage [ 3 ]. This has prompted the development of alternative devices, one such example being the Zero-profile augmented screw implants (Z-P) ​[ 5 ]​.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation